What proportion of patients at the end of life contact out-of-hours primary care? A data linkage study in Oxfordshire. Issue 4 (30th April 2018) - Brettell, Rachel; Fisher, Rebecca; Hunt, Helen; Garland, Sophie; Lasserson, Daniel; Hayward, Gail
Abstract : Objectives: Out-of-hours (OOH) primary care services are a key element of community care at the end of life, yet there have been no previous attempts to describe the scope of this activity. We aimed to establish the proportion of Oxfordshire patients who were seen by the OOH service within the last 30 days of life, whether they were documented in a palliative phase of care and the demographic and clinical features of these groups. Design: Population-based study linking a database of patient contacts with OOH primary care with the register of all deaths within Oxfordshire (600 000 population) during 13 months. Setting: Oxfordshire. Participants: Between 1 December 2014 and 30 November 2015 there were 102 877 OOH contacts made by 67 943 patients with the OOH service. Main outcome measures: Proportion of patients dying in the Oxfordshire population who were seen by the OOH service within the last 30 days of life. Demographic and clinical features of these contacts. Results: 29.5% of all population deaths were seen by the OOH service in the last 30 days of life. Among the 1530 patients seen, patients whose palliative phase was documented (n=577, 36.4%) were slightly younger (median age=83.5 vs 85.2 years, P<0.001) and were seen closer to death (median days to death=2 vs 8, P<0.001). More were assessed at home (59.8% vs 51.9%, P<0.001) and less were admitted to hospital (2.7% vs 18.0%, P<0.001). Conclusions: OOH services see around one-third of all patients who die in a population. Most patients at the end of life are not documented as palliative by OOH services and are less likely to receive ongoing care at home.